Analisis Kandungan Zat Gizi dalam Pembuatan Olahan Snack Dari Ubi Jalar Ungu (Ipomoea batatas L.) - Namirah Yasmine Raudah; Miftahul Khairani; M Rizki; Rizka Lucy Nadia (STIKes Ibnu Sina Ajibarang, 2024)
Purple sweet potato (Ipomoea batatas L.) is a tuber plant that has great potential in providing nutrients and energy sources for humans which is rich in carotenoids, vitamins, minerals, fiber and phytochemical compounds. The aim of this research is to analyze the content of carbohydrates, protein, fat, fiber, vitamins, minerals and other bioactive compounds in processed purple sweet potato foods. The data collection technique used is through an experimental-based qualitative approach, namely by conducting trials in the form of making a new product to become a snack called purple sweet potato balls containing chocolate which is then supported by primary and secondary data. The results obtained are that purple sweet potatoes have a lot of nutritional content consisting of 22.64% starch, fat (0.94%), protein (0.77%), fiber (3.00%), Vitamin C ( 21.43 mg/100 gr), and anthocyanins (110.51 mg/100 gr). So it can be concluded that purple sweet potatoes are useful in preventing heart disease, helping maintain body weight, preventing cancer, maintaining eye health, and minimizing the risk of inflammation.